Fatal Measles Inclusion-Body Encephalitis in Adult with Untreated AIDS, France - Christophe Rodriguez (Emerging Infectious Diseases, 2020)
We report a fatal case of measles inclusion-body encephalitis occurring in a woman from Romania with AIDS. After an extensive but unsuccessful diagnostic evaluation, a pan-pathogen shotgun metagenomic approach revealed a measles virus infection. We identified no mutations previously associated with neurovirulence.